The Protective Effects of 5-Methoxytryptamine-α-lipoic Acid on Ionizing Radiation-Induced Hematopoietic Injury - Deguan Li (International Journal of Molecular Sciences, 2016)
Antioxidants are prospective radioprotectors because of their ability to scavenge radiation-induced reactive oxygen species (ROS). The hematopoietic system is widely studied in radiation research because of its high radiosensitivity. In the present study, we describe the beneficial effects of 5-methoxytryptamine-α-lipoic acid (MLA), which was synthesized from melatonin and α-lipoic acid, against radiation-induced hematopoietic injury. MLA administration significantly enhanced the survival rate of mice after 7.2 Gy total body irradiation. The results showed that MLA not only markedly increased the numbers and clonogenic potential of hematopoietic cells but also decreased DNA damage, as determined by flow cytometric analysis of histone H2AX phosphorylation. In addition, MLA decreased the levels of ROS in hematopoietic cells by inhibiting NOX4 expression. These data demonstrate that MLA prevents radiation-induced hematopoietic syndrome by increasing the number and function of and by inhibiting DNA damage and ROS production in hematopoietic cells. These data suggest MLA is beneficial for the protection of radiation injuries.